2023
DOI: 10.20452/pamw.16522
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure with reduced, mildly reduced and preserved ejection fraction: outcomes and predictors of prognosis

Abstract: 1980-2010, an increasing number of deaths from HF was documented in a standardized population. 3 The same trend has been observed in an analysis of the Polish national database in subsequent years. 4 Furthermore, Pikala et al 5 analyzed the years 2000-2014, and found out a decreasing trend in the standard expected years of life lost per living person from cardiovascular diseases, for both men and women. This is also true for the main cardiovascular diseases, such as INTROduCTION Heart failure (HF) still remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…We found that the most prevalent type of HF was HFrEF, followed by HFpEF and HFmrEF. Similar proportions were described by Rywik et al [5,6]. These findings differ from the ESC Heart Failure Long-Term Registry data, where HFmrEF (24.2%) was found more often than HFpEF (16.0%), with 59.8% of HFrEF patients [7].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We found that the most prevalent type of HF was HFrEF, followed by HFpEF and HFmrEF. Similar proportions were described by Rywik et al [5,6]. These findings differ from the ESC Heart Failure Long-Term Registry data, where HFmrEF (24.2%) was found more often than HFpEF (16.0%), with 59.8% of HFrEF patients [7].…”
Section: Discussionsupporting
confidence: 71%
“…All-cause mortality in our study was highest in HFrEF patients, followed by HFmrEF and HFpEF. No differences in one-year mortality between HFmrF and HFpEF patients were found, which was confirmed in another study conducted in the Polish population by Rywik et al [5,6]. It may be explained by the differences in death causes between HF groups.…”
Section: Discussionsupporting
confidence: 69%